The Application of Discounted Cash Flow Valuation Method Towards Adaptive Fashion Company in Indonesia - Maulana, Rizki Firman; Irawan, Atika (Proceedings International Conference on Education Innovation and Social Science, 2023)
People with disabilities (PWDs) often experience difficulties in carrying goods, moreover there are issues related to inclusiveness in the field of fashion which may limit their space for expression in this field. For this reason, a startup company called Beyond is here to address this issue by providing fashionable adaptive bags for wheelchair users in Indonesia. With the booming trend for local businesses and the high rate of habitual buying of goods and accessories owned by Indonesians, Beyond has a huge opportunity in the market. However, this company does not yet know the valuation even though this is very necessary to increase capital for Beyond's business continuity. As a result of this research, the valuation of Beyond is measurable, namely IDR 510,736,887 equivalent to 1021.47% of the initial investment value.